The Novelties in the Novel “Sang Keris”: An Intertextual Study - Anggit Febrianto (Universitas Brawijaya, 2021)
This research is aimed to prove that old literature helps the creation of modern literary works, such as providing inspiration, assisting authors in making themes, characterizations, motives, and so on. One of the modern literary works inspired by old literary works is the novel titled Sang Keris. Reading this 107 pages novel, we will feel a very thick Javanese nuance. By using the intertextual approach, this paper will focus on discussing the